Rejection and victimization by peers in children with intellectual disability and autism spectrum disorder - Emerich, Deisy Ribas (2017)
Children with special educational needs, such as Intellectual Disability (ID) and Autism Spectrum Disorders (ASD), are increasingly participating in regular classes. Despite the relevance of this inclusion, these children may face difficulties as rejection and victimization by peers. Through a literature review, this work aimed to identify the prevalence, impact and factors associated with rejection and victimization among children with DI and TEA. The search was conducted in the Web of Science, PubMed, Medline, Lilacs and Scielo, using the keywords: rejection by peers, peer victimization, intellectual disabilities, Autism Spectrum Disorder , children with disabilities and special needs. We identified 196 articles, of which 32 met the inclusion criteria. We verified high prevalence of victimization and rejection among children with special educational needs, regardless of age. Deficits in social skills and executive functions, inattentive and hyperactive behavior and internalizing problems were associated with difficulties in relationships with peers in this population. These indicators should be included in prevention and/or treatment programs to enable the proper inclusion of children with special educational needs in regular classrooms.